2004
DOI: 10.2355/isijinternational.44.1125
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Behavior of Hematite to Magnetite under Fluidized Bed Conditions

Abstract: Reduction kinetic tests of Mt. Newman hematite ore from Western Australia were carried out in a laboratory-scale fluidized bed reactor at temperatures from 623 to 873 K and an absolute pressure of 10 bar. The reducing gas mixture was thermodynamically in equilibrium with magnetite and consisted of a mixture of H 2 , H 2 O, CO, CO 2 and CH 4 . The effect of temperature and residence time was studied. The original ore and its mineralogical and petrographical changes with increasing reduction time were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…Reduction of hematite in fluidized bed reactor was demonstrated also by authors in Feilmayr et al [7]. The authors have reported the effect of the temperature and residence time on the reduction rate.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Reduction of hematite in fluidized bed reactor was demonstrated also by authors in Feilmayr et al [7]. The authors have reported the effect of the temperature and residence time on the reduction rate.…”
Section: Introductionmentioning
confidence: 56%
“…Newman (Feilmayr et al [7]) was used as the ore sample and hydrogen as reducing agent. Argon was used for the initial phase of heating of the test unit.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reducing gas CO diffused through the boundary layer, reaching the external surface of the hematite particles and continuing further into the micropores to the internal surface of the hematite grains. The phase-interface reaction described by Equation (1) occurred at this surface, where the reducing gas picked up oxygen and freed two electrons [9,11,29]:…”
Section: Physical and Chemical Processesmentioning
confidence: 99%
“…Fluidized reduction roasting has been proven to bean industrially economical and efficient method for the chemical synthesis of magnetite, with hematite as the raw material [9,10]. The reaction in fluidized bed reactors offers the advantages of a uniform temperature in the reactor, and of fast heat and mass transfer [11].…”
Section: Introductionmentioning
confidence: 99%